Level of soft skill in the implementation of work-based learning among community college students - Ali, Azita; Mahmod, Shuhada (2018)
The issue of graduate unemployment often crops up in the mass media; and more often than not, the discussions have centred on the failure of tertiary educational institutions to churn out quality graduates. Thus, the method of work-based learning (WBL) is seen as a way to improve the soft skills of the graduates. The study was conducted using quantitative research survey; the design of the study used an adapted questionnaire as an instrument. Data were analysed using Statistical Package of Social Science (SPSS) version 20. The respondents consisted of 97 students who attended WBL programmes at a community college. Descriptive statistics was used to extract data from the questionnaires for the calculation of mean. The findings reveal that the level of soft skills among community college students was high, and they include these abilities: communication skills, problem-solving skills, learning and information management, professional ethics skills and leadership skills.